Sustainability Report terhadap Nilai Perusahaan: Studi Perusahaan yang Terdaftar dalam Sustainability Report Rating - Apriani Dorkas Rambu Atahau; Marino Firaj Kausar (Postgraduate Program Merdeka University, 2022)
This study aims to determine how the influence of the disclosure of sustainability reports in the economic, environmental, and social fields on firm value in companies that follow the Asia Sustainability Report Rating. In this study, the research population is a company listed in the Asia Sustainability Report Rating period 2018-2020. There are 59 companies registered in the 2018-2020 period. Determination of the research sample using purposive sampling where the limitations of the selected sample are based on certain criteria. In this study using regression as an analytical technique. The results of this study indicate that the disclosure of sustainability reports in the economic and environmental fields has a significant positive effect on firm value. Meanwhile, the disclosure of sustainability re-ports in the social sector has no effect on Company Value.DOI: https://doi.org/10.26905/afr.v5i2.7810